Sociodemographic factors associated with major depressive episodes and suicidal ideation among emerging adults with diabetes in the U.S - Yadav, Sandhya; Hong, Young-Rock; Westen, Sarah; Marlow, Nicole M.; Haller, Michael J.; Walker, Ashby F. (Frontiers in Endocrinology, 2023)
Background Research focused on disparities related to mental health comorbidities, especially among emerging adults with diabetes, is limited. Identifying associated factors of disparities could inform policy decisions to make diabetes-related interdisciplinary care more accessible for vulnerable groups. Method Using data from the National Survey on Drug Use and Health (2015-2019), we examined disparities in presence of major depressive episode (MDE) and suicidal ideation among emerging adults with diabetes. Survey design-adjusted bivariate and multivariable logistic regression models were used for statistical analyses. Results The study included 1,125 emerging adults (18-25 years old), with a history of type 1 diabetes (T1D) or type 2 diabetes (T2D). After controlling for sociodemographic and health-related characteristics, we found lower odds of having past-year major MDE for non-Hispanic Black (AOR, 0.42, p=0.032) compared to their non-Hispanic White counterparts. Females were 3.02 times more likely to have past-year MDE than males (AOR, 3.02, p=0.004). The odds of having past-year MDE were 1.96 times higher among individuals who identified as LGB (lesbian, gay, bisexual) (AOR, 1.96, P=0.038). There were no statistically significant disparities in suicidal ideation related to race/ethnicity, sex, education, and family income. However, individuals who identified as LGB had significantly higher likelihood of suicidal ideation than their heterosexual counterparts (AOR, 2.47, P=0.004). Conclusion Significant disparities related to MDE and suicidal ideation exist based on race/ethnicity, gender, and sexual orientation. Integration of a mental health professional into the multidisciplinary diabetes care team is critical for effective management of comorbid mental health conditions in younger patients with diabetes.